2017
DOI: 10.1142/s0218202517500154
|View full text |Cite
|
Sign up to set email alerts
|

A quest toward a mathematical theory of the dynamics of swarms

Abstract: This paper presents a unified mathematical theory of swarms where the dynamics of social behaviors interacts with the mechanical dynamics of self-propelled particles. The term behavioral swarms is introduced to characterize the specific object of the theory which is subsequently followed by applications. As concrete examples for our unified approach, we show that several Cucker-Smale type models with internal variables fall down to our framework. Subsequently the modeling goes beyond the Cucker-Smale approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(63 citation statements)
references
References 62 publications
0
63
0
Order By: Relevance
“…The obtained results confirmed that cells tend to follow paths and to align according to the ECM structure. In this sense, it is worth noticing the analogy with crowd dynamics [33], vehicular traffic [34], or swarming phenomena [37], where individual entities also receive some stimulus from the surrounding environment, interact among themselves, and generate certain emergent behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained results confirmed that cells tend to follow paths and to align according to the ECM structure. In this sense, it is worth noticing the analogy with crowd dynamics [33], vehicular traffic [34], or swarming phenomena [37], where individual entities also receive some stimulus from the surrounding environment, interact among themselves, and generate certain emergent behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Some specific tools of the KTAP approach have so far been used in many other applications. For instance, competition between tumor and immune cells [30] and social dynamics [31,32], crowd dynamics [17,18,[33][34][35][36], and swarming [37]. Thus, the contents of this paper may be useful for the modeling of other phenomena in life sciences.…”
mentioning
confidence: 99%
“…Remark 2.2 Proposition 2.1 is based only on the structure of the CS system, and holds for any non-negative communication weight ψ. The symmetry of x → ψ(|x|) allows to swap indexes in (6).…”
Section: Definition 21mentioning
confidence: 99%
“…al. [70] form 1995, extensive studies were carried out in various directions including: asymptotics [24,31], pattern formation [54,55], collision avoidance [1,22], variants of the model with preferences [23,45], leadership [21,59] and additional deterministic or stochastic forces [6,7,15,28]. Further directions include the study of the kinetic [9,31,32] and hydrodynamic [29,30,40] limits of the CS particle system and their coupling with classical equations of hydrodynamics [2,3,17,52].…”
Section: Introductionmentioning
confidence: 99%
“…The interested reader is referred to the book [3] for theoretical aspects and for the rationale to develop specific applications which have been produced to model, for instance, the dynamics of collective learning [4], the immune competition [5], vehicular traffic [6][7][8], the dynamics of crowds [9][10][11], and the collective motion of swarms [12].…”
Section: Introductionmentioning
confidence: 99%